A power system stabilizer design by big bang-big crunch algorithm - Dincel, Emre; Istemihan Genc, V. M. (IEEE, 2012)
Power system stabilizers (PSSs) are used to enhance damping of electromechanical oscillations occurring in power systems after small or large disturbances. PSSs designed by classical control methods have been widely used to accomplish this task. In this study, a new method based on big bang-big crunch algorithm is proposed to optimize the parameters of PSSs with a conventional structure in order to stabilize the system and to increase damping of this type of oscillations. The success of the proposed method is demonstrated on a two-area test system through simulations in which both local and inter-area oscillations are effectively damped.